Antenatal reflex DNA screening for trisomy 18 and trisomy 13 in addition to Down's syndrome. (December 2016) - Bestwick, Jonathan P; Wald, Nicholas J
Objective: Antenatal reflex DNA screening for Down's syndrome has a high screening performance. We aimed to determine the performance of trisomy 18 and trisomy 13 reflex DNA screening when added to Down's syndrome screening. Methods: In our modelled screening protocol, women provide two samples: a serum sample for a Combined test and a plasma sample for a possible DNA test. Women with Down's syndrome, trisomy 18, or trisomy 13 Combined test risks above a single cut-off have a reflex DNA test using the plasma sample, without the need to recall them to collect another sample and provide counselling. Women with a failed DNA test (after a second attempt using a fresh plasma sample) have an Integrated test, and are classified as positive if any of the Down's syndrome, trisomy 18, or trisomy 13 Integrated test risks are greater than 1 in 25. Results: At 1 in 800 term risk cut-offs for Down's syndrome, trisomy 18, and trisomy 13, an estimated 10% of women are reflexed to DNA screening, yielding a 91% Down's syndrome detection rate, an 89% trisomy 18 detection rate, and a 79% trisomy 13 detection rate for a 0.05% false-positive rate. At a 1 in 1900 term risk cut-off for Down's syndrome, trisomy 18, or trisomy 13, an estimated 20% of women are reflexed to DNA screening, and this yields a 94% Down's syndrome detection rate, a 92% trisomy 18 detection rate, and an 84% trisomy 13 detection rate for a 0.10% false-positive rate. Conclusion: Reflex DNA screening for trisomies 18 and 13 can be usefully added to reflex DNA screening for Down's syndrome.